Constraining the parameter space for the solar nebula: the effect of disk properties on planetesimal formation - Lenz, Christian Tobias; Klahr, Hubert; Birnstiel, Tilman; Kretke, Katherine; Stammler, Sebastian (Astronomy and astrophysics, 2020)
Context: When we wish to understand planetesimal formation, the only data set we have is our own Solar System. The Solar System is particularly interesting because so far, it is the only planetary system we know of that developed life. Understanding the conditions under which the solar nebula evolved is crucial in order to understand the different processes in the disk and the subsequent dynamical interaction between (proto-)planets after the gas disk has dissolved.Aims. Protoplanetary disks provide a plethora of different parameters to explore. The question is whether this parameter space can be constrained, allowing simulations to reproduce the Solar System. Methods: Models and observations of planet formation provide constraints on the initial planetesimal mass in certain regions of the solar nebula. By making use of pebble flux-regulated planetesimal formation, we performed a parameter study with nine different disk parameters such as the initial disk mass, the initial disk size, the initial dust-to-gas ratio, the turbulence level, and others. Results: We find that the distribution of mass in planetesimals in the disk depends on the timescales of planetesimal formation and pebble drift. Multiple disk parameters can affect the pebble properties and thus planetesimal formation. However, it is still possible to draw some conclusions on potential parameter ranges. Conclusions: Pebble flux-regulated planetesimal formation appears to be very robust, allowing simulations with a wide range of parameters to meet the initial planetesimal constraints for the solar nebula. This means that it does not require much fine-tuning.